An Evaluation of the Safety and Efficacy of Simultaneous Bilateral Nephrectomy and Renal Transplantation for Polycystic Kidney Disease: A 20-Year Experience. Issue 11 (November 2017) - Grodstein, Elliot I.; Baggett, Nathan; Wayne, Shawn; Leverson, Glen; D'Alessandro, Anthony M.; Fernandez, Luis A.; Foley, David P.; Mezrich, Joshua D.; Odorico, Jon S.; Redfield, Robert R.; Sollinger, Hans W.; Kaufman, Dixon B.
Abstract : Background: Many strategies regarding timing of native nephrectomies exist for patients with symptomatic polycystic kidney disease (PCKD). Methods: This is a single-center, retrospective study of 594 adults with PCKD who had renal transplants from 1994 to 2014. Three groups were analyzed: renal transplant-only recipients (tx alone), recipients of simultaneous bilateral nephrectomies and transplant (simultaneous), and recipients with pretransplant bilateral nephrectomies (pre). The primary outcome was graft survival. Secondary outcomes included postoperative complications. Results: Five hundred sixty-five adults with PCKD received kidney transplants (303 tx alone, 161 simultaneous, 27 pre). Ten-year posttransplant graft survival was 68.5%, 63.6%, and 65.7% for tx alone, simultaneous, and precohorts ( P = 0.86). No statistically significant differences were observed in rates of postoperative ileus, deep vein thrombosis, small bowel obstruction, urinary stricture, urine leak, hernia formation, and delayed graft function. More wound complications were seen in prepatients (25.9% vs 11.1% tx alone, 5.1% simultaneous; P = 0.03), whereas simultaneous patients had a lower incidence of lymphocele (1.3% vs 11.1% pre, 10.2% tx-alone; P = 0.002). Importantly, simultaneous patients had more renal vascular thromboses (4.4% vs 1.3% tx alone, 0% pre; P = 0.04). 16.3% of renal transplant alone patients required nephrectomy at 10 years follow-up. Twenty-nine patients were referred for transplant having had nephrectomies and were ultimately not transplanted. In 4 of these patients who had data available for analysis, the mean panel-reactive antibody significantly increased after nephrectomy was performed. Conclusions: Simultaneous bilateral nephrectomy can be safely performed at the time of renal transplantation, however, carries a significantly increased risk of renal vascular thrombosis. Abstract : Simultaneous bilateral nephrectomy for patients with symptomatic polycystic kidney disease can be safely performed at the time of renal transplantation; however, it carries a significantly increased risk of renal vascular thrombosis compared with the recipients with renal transplant-only or pretransplant bilateral nephrectomies.